ANALISIS PEMBENTUKAN PERSONAL BRANDING IBNU WARDANI SEBAGAI CONTENT FLEXING INFLUENCER PADA AKUN SOSIAL MEDIA TIKTOK - Cyntia Dewi Anggraini; Ahmad Fiqri Pratama (Jurnal Riset Multidisiplin Edukasi, 2025)
In modern ages like now, personal branding has a very important role in facilitating an individual in making relationships in the world of work. Ibnu Wardani uses Tiktok social media as a forum for forming personal branding as an influencer and content flexing. The purpose of this research is to anlyze establishment of personal branding of Ibnu Wardani as a content flexing influencer on Tiktok social media accounts. The method used in this research uses a qualitative approach by conducting a descriptive study by collecting data through a literature study. The author uses eight laws of personal branding. Based on the results discussed regarding the eight laws of personal branding according to Peter Montoya, Ibnu Wardani through his personal Tiktok social media has not fulfilled these eight concepts. Of the eight personal branding concepts of Peter Montoya, Ibnu Wardani has not complete one of the elements, namely Leadership (The Law of Leadership) because Ibnu Wardani has not highlighted his excellence, does not have a great influence on society, and/or recognition as a leader in the society.